2005
DOI: 10.1074/jbc.m501163200
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Functional Study of the Viral Telomerase RNA Based on Natural Mutations

Abstract: Telomerase activity is present in most malignant tumors and provides a mechanism for the unlimited potential for division of neoplastic cells. We previously characterized the first identified viral telomerase RNA (vTR) encoded by the Marek's disease virus (MDV) (Fragnet, L., Blasco, M. A., Klapper, W., and Rasschaert, D. (2003) J. Virol. 77, 5985-5996). This avian herpesvirus induces T-lymphomas. We demonstrated that the vTR subunit of the oncogenic MDV-RB1B strain is functional and would be more efficient tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 33 publications
2
45
0
1
Order By: Relevance
“…Moreover, deletion of the two copies of the vTR gene induces a decrease of about 60% in tumor incidence in chickens [30]. In vitro studies established the function of vTR with its natural partner, chicken TERT (chTERT), and further demonstrated that vTR and chTERT reconstitute a more active complex than the native one (chTR/chTERT) [33]. Although the alignment of the primary sequences of vTR and hTR reveals only a weak sequence homology (30%; data not shown), the overall secondary structure predicted for vTR shows high similarity to the consensus functional structures described for hTR, including the conserved regions CR1 to CR8 [28,34,35].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, deletion of the two copies of the vTR gene induces a decrease of about 60% in tumor incidence in chickens [30]. In vitro studies established the function of vTR with its natural partner, chicken TERT (chTERT), and further demonstrated that vTR and chTERT reconstitute a more active complex than the native one (chTR/chTERT) [33]. Although the alignment of the primary sequences of vTR and hTR reveals only a weak sequence homology (30%; data not shown), the overall secondary structure predicted for vTR shows high similarity to the consensus functional structures described for hTR, including the conserved regions CR1 to CR8 [28,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…It was then subcloned into the pUC-119 vector, which had been previously digested with XbaI/PstI. The chTR gene under the control of the T7 promoter was obtained from the XbaI/PstI digestion of pBS-T7chTR [33], and directly cloned in the pUC-119 vector. All intermediate and final constructs were sequenced with appropriate primers to check the integrity of the T7 promoter and genes of interest.…”
Section: Constructsmentioning
confidence: 99%
See 3 more Smart Citations